EFFECTIVE SILICON DEVICE STRUCTURES WITH RADIATIVE RECOMBINATION ON DISLOCATIONS - A. V. Mudryi; V. D. Zhivulko; F. Mofidnakhaei; G. D. Ivlev; M. V. Yakushev; R. W. Martin; A. V. Dvurechenskii; V. A. Zinovyev; Zh. V. Smagina; P. A. Kuchinskaja (Приборы и методы измерений)
The efficient electroluminescence in the region of band-to-band (1,1 eV) and dislocationrelated (D1 – 0,8 eV) transitions has been detected from Si p-n structures at room and liquid nitrogen temperatures. It was found that dislocation-related luminescence in Si single crystals is considerably stronger than the intrinsic band-to-band emission in the wide temperature range of 4,2–300 K. The temperature dependent measurement of the D1 photoluminescence intensity shows that two energy levels placed below the conduction (0,04 eV) and above valence (0,32 eV) bands are responsible for this radiative recombination on dislocations.